Discovery of the source HESS J1356-645 associated with the young and energetic PSR J1357-6429 - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Becherini, Y.; Becker, J.; Behera, B.; et al. (Astronomy & Astrophysics, 2011)
Context. Several newly discovered very-high-energy (VHE; E > 100 GeV) γ-ray sources in the Galaxy are thought to be associated with energetic pulsars. Among them, middle-aged (10 yr) systems exhibit large centre-filled VHE nebulae, offset from the pulsar position, which result from the complex relationship between the pulsar wind and the surrounding medium, and reflect the past evolution of the pulsar. Aims. Imaging Atmospheric Cherenkov Telescopes (IACTs) have been successful in revealing extended emission from these sources in the VHE regime. Together with radio and X-ray observations, this observational window allows one to probe the energetics and magnetic field inside these large-scale nebulae. Methods. H.E.S.S., with its large field of view, angular resolution of 0.1° and unprecedented sensitivity, has been used to discover a large population of such VHE sources. In this paper, the H.E.S.S. data from the continuation of the Galactic Plane Survey (-80° < < 60°, |b| < 3°), together with the existing multi-wavelength observations, are used. Results. A new VHE γ-ray source was discovered at RA (J2000) = 135600, Dec (J2000) =-64°30′00′′ with a 2′ statistical error in each coordinate, namely HESS J1356-645. The source is extended, with an intrinsic Gaussian width of (0.20 ± 0.02)°. Its integrated energy flux between 1 and 10 TeV of 8 × 10 erg cm s represents ∼11% of the Crab Nebula flux in the same energy band. The energy spectrum between 1 and 20 TeV is well described by a power law dN/dE E with photon index Γ = 2.2 ± 0.2 ± 0.2. The inspection of archival radio images at three frequencies and the analysis of X-ray data from ROSAT/PSPC and XMM-Newton/MOS reveal the presence of faint non-thermal diffuse emission coincident with HESS J1356-645. Conclusions. HESS J1356-645 is most likely associated with the young and energetic pulsar PSR J1357-6429 (d = 2.4 kpc, τ = 7.3 kyr and Å-= 3.1 × 10 erg s), located at a projected distance of ∼5 pc from the centroid of the VHE emission. HESS J1356-645 and its radio and X-ray counterparts would thus represent the nebula resulting from the past history of the PSR J1357-6429 wind. In a simple one-zone model, © 2011 ESO.
Keywords: gamma rays: general; ISM: individual objects: HESS J1356-645; ISM: individual objects: PSR J1357-6429; surveys

Erratum: "Search for Dark Matter Annihilation Signals from the Fornax Galaxy Cluster with H.E.S.S.'' (2012, ApJ, 750, 123) - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Barres De Almeida, U.; Becherini, Y.; Becker, J.; Behera, B.; Bernlöhr, K.; et al. (Astrophysical Journal, 2014)

Measurement of the extragalactic background light imprint on the spectra of the brightest blazars observed with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
The extragalactic background light (EBL) is the diffuse radiation with the second highest energy density in the Universe after the cosmic microwave background. The aim of this study is the measurement of the imprint of the EBL opacity to γ-rays on the spectra of the brightest extragalactic sources detected with the High Energy Stereoscopic System (H.E.S.S.). The originality of the method lies in the joint fit of the EBL optical depth and of the intrinsic spectra of the sources, assuming intrinsic smoothness. Analysis of a total of ∼10γ-ray events enables the detection of an EBL signature at the 8.8σ level and constitutes the first measurement of the EBL optical depth using very-high energy (E > 100 GeV) γ-rays. The EBL flux density is constrained over almost two decades of wavelengths [0.30 μm, 17 μm] and the peak value at 1.4 μm is derived as λF = 15 ± 2 ± 3 nW m sr. © 2013 ESO.
Keywords: BL Lacertae objects: general; Cosmic background radiation; Gamma rays: galaxies